Intervention of TLR4 Signal Pathway Cytokines in Severe Liver Injury with Obstructive Jaundice in Rats - Lin, L.; Cai, W. M.; Qin, C. J.; Miao, L. C.; Yun, L. T.; Hua, Y.; Weilin, L. (International Journal of Sports Medicine, 2012)
Obstructive jaundice is a common surgical disease and a variety of end-stage severe liver injuries still lack effective treatments. Compared to traditional liver transplantation therapy, herbal treatment is noninvasive and has fewer side effects. Research results have shown that a modified major decoction of bupleurum can reduce the toxic reaction of obstructive jaundice, even though the mechanism is unclear. A period of chronic exercise training can significantly reduce TLR4 expression in mononuclear cells and the secretion of inflammatory cell factors. Our study administered a modified major decoction of bupleurum in combination with exercise in rats with obstructive jaundice and the results indicated that applying a major bupleurum decoction in combination with moderately intense aerobic exercise showed a beneficial effect on adjusting the expression of liver inflammatory cytokines, which thus improved immunity and finally reduced the liver injury of rats with obstructive jaundice.
Keywords: modified major decoction of bupleurum; medium-intensity aerobic exercise; obstructive jaundice; TLR4